2020
DOI: 10.1016/j.jbiotec.2020.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Selection of chromatographic methods for the purification of cell culture-derived Orf virus for its application as a vaccine or viral vector

Abstract: Highlights Estimation of the isoelectric point and size of Vero cell-derived Orf virus. Limited dynamic binding capacity of tested Orf virus to sulfated cellulose. Purification of Orf virus by steric exclusion chromatography lead to 84 % recovery. Hydrophobic interaction chromatography suitable for Orf virus purification. Promising unit operations for a scalable DSP to produce Orf virus viral vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 64 publications
0
33
1
Order By: Relevance
“…For comparative reasons, the CP were chosen to be spherical and of an average size (190 nm) of viruses, which were successfully purified by the SXC in previous studies [ 15 , 17 , 19 ]. In order to characterize the CP aggregation behavior, the pH-and PEG 8000 -dependent size and charge distributions were assessed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For comparative reasons, the CP were chosen to be spherical and of an average size (190 nm) of viruses, which were successfully purified by the SXC in previous studies [ 15 , 17 , 19 ]. In order to characterize the CP aggregation behavior, the pH-and PEG 8000 -dependent size and charge distributions were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…All SXC experiments were conducted on an Äkta Pure 25 (Cytiva, Marlborough, MA, USA) with online UV (260 nm), pre-column pressure, and dynamic light scattering (DLS) (Nano DLS Particle Size Analyzer, Brookhaven Instruments, Holtsville, NY, USA) monitoring, controlled via the Unicorn 7.1 software (Cytiva, Marlborough, MA, USA). The execution of the SXC runs was adapted from Lothert et al [ 17 ] with minor adjustments. In short, the single-use adsorbent was a stack of ten layers of regenerated cellulose membranes (Whatman, Maidstone, UK), 13 mm in diameter and 1 µm nominal pore size, inserted into a stainless-steel filter holder (Pall Life Sciences, Port Washington, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell factor (described in Section 2.2-2) used to convert the permittivity signal to an online viable cell concentration was equal to 0.57, 0.65, and 0.44 for run 1, run 2, and the perfusion control run, respectively adenovirus (Fernandes et al, 2013;Moleirinho et al, 2020), 41% for MVA (Léon et al 2016), 52% for influenza virus , and 20%-60% for AAV production (Moleirinho et al, 2020;Terova et al, 2018) were reported. Successful application of membrane-based SXC for influenza virus, yellow fever virus, AAV, baculovirus, hepatitis C virus, and Orf virus purifications have been reported (Lothert, Offersgaard, et al, 2020;Lothert, Pagallies, et al, 2020;Lothert, Sprick, et al, 2020;Marichal-Gallardo et al, 2021;Marichal-Gallardo, 2019). This suggests that the integrated process established here may also be transferrable to other virus manufacturing processes (Bissinger et al, 2021).…”
Section: Discussionmentioning
confidence: 99%